Retribution - Walden, Mark (Walden, Mark. Earthfall trilogy, 2016)
Twelve-year-old Sam and his band of children survivors of the alien invasion discover another group of alien resistors run by a man named Mason who is recruiting an army to fight the aliens. Sam joins the group to disable alien technology in Tokyo, but quickly learns that something worse than the aliens--something old and evil--is coming to destroy them all.